The economic world balance - Kristensen, Thorkil; The Foreign Policy Society (Copenhagen : Munksgaard; Amsterdam : North-Holland, 1960)
A study by the Danish Foreign Policy Society appraising the economic status and possible economic trends, in the main regions of the world. It include topics like: factors of growth; population and labour force; capital; nature; culture; models of growth among others.
At head of title: The Foreign Policy Society.
Includes index.
Includes bibliographical references: p. 358-365.
lje 07/05/2018
Loans
Keywords: Economic history